Potenciais fatores associados com o desempenho de carteira das entidades fechadas de previdência complementar brasileiras - Silva, William Aparecido Maciel da (2019)
Closed Entities of Complementary Pension Plans (EFPC) are foundations or a non-profit corporation that maintains collective pension plans. The performance of EFPC investments, as well as other forms of investment, is traditionally divided into risk and return components, so that the return on the investment portfolio is influenced by the allocation and selection of assets. Thus, having as a support would have of portfolio theory of Markowitz (1952), the present study aimed to verify potential factors that may affect the portfolio performance of closed Brazilian private pension entities between the period of Dec./2010 to Dec./2017. For the calculation of the Sharpe Index the sample was 311 EFPCs. The sample was divided into two stages due to the occurrence of missing values, being 283 observations for the simultaneous analysis of the variables: Size; Age; Number of Participants and 130 observations for the simultaneous analysis of all variables considered in the study. To do so, previous studies based on the performance of national and international EFPCs and identified potential factors in the literature that may influence the performance of EFPC have been described. As main results, it was verified that there is no homogeneity in risk premiums, evidencing that the EFPC investment allocation strategy varies according to the need of each entities. On average, EFPC performance was positive in relation to the benchmark with a low risk-return ratio, evidencing that the EFPC could take greater risks in allocating their portfolios, which could, as the case may be, provide higher average returns. The results obtained by the multivariate linear regression showed that among the variables that can influence performance, the Administration Fee, Age of the EFPC, and Number of Participants present statistical significance to explain the performance of EFPC. Thus, it is concluded from the portfolio theory perspective that EFPC, investment policy can limit performance by leaving EFPCs exposed to conservative asset classes.